How do we meet the spiritual needs of residents in aged care facilities? - Smith, Jodi Maree (Curtin University, 2013)
A descriptive qualitative approach was used to explore the spiritual needs of residents (n=16) living in a residential aged care facility in regional Western Australia. A constant comparison method of analysis identified three central themes: spirituality - I don’t know what you mean; end of life is no joy at all and sources of support. This study adds to a broader understanding of the issues associated with ageing from the residents’ perspective.